Three years of wastewater surveillance for new psychoactive substances from 16 countries ... - Bade, Richard; Rousis, Nikolaos; Sangeet Adhikari; Baduel, Christine; Lubertus Bijlsma; Bizani, Erasmia; Boogaerts, Tim; Burgard, Daniel A.; Castiglioni, Sara; Chappell, Andrew; Covaci, Adrian; Driver, Erin M.; et al. (Zenodo, 2023)
The proliferation of new psychoactive substances (NPS) over recent years has made their surveillance complex. The analysis of raw municipal influent wastewater can allow a broader insight into community consumption patterns of NPS. This study examines data from an international wastewater surveillance program that collected and analysed influent wastewater samples from up to 47 sites in 16 countries between 2019 and 2022. Influent wastewater samples were collected over the New Year period and analysed using validated liquid chromatography – mass spectrometry methods. Over the three years, a total of 18 NPS were found in at least one site. Synthetic cathinones were the most found class followed by phenethylamines and designer benzodiazepines. Furthermore, two ketamine analogues, one plant based NPS (mitragynine) and methiopropamine were also quantified across the three years. This work demonstrates that NPS are used across different continents and countries with the use of some more evident in particular ... : The authors sincerely thank the wastewater treatment plant operators for their help in collecting samples and the support provided by the lab staff who performed the extraction of the samples. The authors also thank SCIEX for the use of their instrument and Liam O'Brien for his statistical advice. The University of Iceland wants to particularly acknowledge Efla hf. and Veitur ohf. for their assistance with sample collection. SLU acknowledges the support of Inga Haalck, Oscar G¨otlind and Gabriel Persson for sample collection. IGE acknowledges the support of Nelly Laforet and Myriam Millet-Perrin for sample collection. The Queensland Alliance for Environmental Health Sciences, The University of Queensland, gratefully acknowledges the financial support of the Queensland Department of Health. R. B. is the recipient of an Australian Research Council Discovery Early Career Award (project number DE220100381), and J. M. is the recipient of an Australian Research Council Australian Laureate Fellowship (project ...